2021
DOI: 10.3126/tuj.v36i01.43584
|View full text |Cite
|
Sign up to set email alerts
|

Brand Preference of Professionals towards Choosing Smartphone in Nepal

Abstract: It is tough to forecast or assess an individual preference, but it is vital for marketers since it represents an essential step in understanding consumer choice. It is critical to determine brand preference based on the awareness of the customer. The primary objectives of this study are to assess how professional consumers prefer brands in the choice of mobile phones. Business people, private jobholders, government personnel, and farmers are considered professionals for this study. Other goals are to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Also, several kinds of literature highlight the importance of using ICT tools including GeoGebra in teaching and learning mathematics. In this sense, Sah (2017) indicated that there is a positive attitude among teachers toward the use of media tools in their classroom teaching. The use of ICT in teaching and learning enhances motivation to make the concepts clear and meaningful in any subject matter (Keong, Horani, & Daniel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Also, several kinds of literature highlight the importance of using ICT tools including GeoGebra in teaching and learning mathematics. In this sense, Sah (2017) indicated that there is a positive attitude among teachers toward the use of media tools in their classroom teaching. The use of ICT in teaching and learning enhances motivation to make the concepts clear and meaningful in any subject matter (Keong, Horani, & Daniel, 2005).…”
Section: Introductionmentioning
confidence: 99%